2021
DOI: 10.3390/ijms22041720
|View full text |Cite
|
Sign up to set email alerts
|

Long, Noncoding RNA SRA Induces Apoptosis of β-Cells by Promoting the IRAK1/LDHA/Lactate Pathway

Abstract: Long non-coding RNA steroid receptor RNA activators (LncRNA SRAs) are implicated in the β-cell destruction of Type 1 diabetes mellitus (T1D), but functional association remains poorly understood. Here, we aimed to verify the role of LncRNA SRA regulation in β-cells. LncRNA SRAs were highly expressed in plasma samples and peripheral blood mononuclear cells (PBMCs) from T1D patients. LncRNA SRA was strongly upregulated by high-glucose treatment. LncRNA SRA acts as a microRNA (miR)-146b sponge through direct sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Here, the conversion from pyruvate to lactate, which is catalyzed by lactate dehydrogenase (LDH) proteins including the androgen receptor target LDHA1 presents a critical step ( 39 ). Current evidence, gathered primarily from studies on beta-cells in pancreatic islets, suggests that LDH release is reduced in the absence of IRAK1 ( 40 ). In cell culture and xenograft tumor models, gain of IRAK1 promotes tumorigenic growth and metastasis of breast, head neck, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the conversion from pyruvate to lactate, which is catalyzed by lactate dehydrogenase (LDH) proteins including the androgen receptor target LDHA1 presents a critical step ( 39 ). Current evidence, gathered primarily from studies on beta-cells in pancreatic islets, suggests that LDH release is reduced in the absence of IRAK1 ( 40 ). In cell culture and xenograft tumor models, gain of IRAK1 promotes tumorigenic growth and metastasis of breast, head neck, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of LDHA could significantly improve DM's glucose metabolism [ 52 ]. Inhibition of LDHA decreased reactive oxygen species production, reduced lactate secretion, and rescued beta-cell apoptosis [ 53 ]. Our results showed that reduced expression of miR-489 in GF group could increase the apoptosis index as determined by flow cytometry in HEK-293 cell.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA SRA was reported [ 41 ] to be overexpressed in the plasma samples of 25 patients with T1D as well as in CD4+ regulatory T cells (Tregs) induced with high glucose in the CD4+ MOLT4 human T lymphoblast cell line. lncRNA SRA modulates the expression of miR-146b, which is downstream of interleukin-1 receptor-associated kinase 1 (IRAK1)/protein kinase B (AKT)/S6 Kinase 1 (S6K1) signaling.…”
Section: Dysregulated Human Ncrnas In Diabetesmentioning
confidence: 99%